English For Tourism Industry: Descriptive Study On Economic Growth Appeal - Taufiq Kurniawan; Ivan Suaidi; Ermawati Ermawati; Riza Laely Ikayanti (Institut Teknologi dan Bisnis (ITB) Semarang, 2023)
In these recent years, tourism is one of the most pivotal sectors to be developed in improving the economy development in the world. The quick development of the tourism and hospitality industry can straightly influence the English language which is the most widely used and spoken language in international tourism in the twenty-first century, including Indonesia. The need for the English skills has a major role in tourism industry especially in supporting socio-economic development. The present paper highlights the importance of English in tourism industry as most of the communications in that sector is done in English. It also reveals how English is being widely used in hospitality as a support of the business progress. This study was conducted in measuring to what extend English becomes one of the most essential factors in improving the tourism industry and plays a significant role in developing economy in West Nusa Tenggara. Interviews and open questionnaires were then conducted as a part of data collection. Five different stakeholders supporting the tourism industry in West Nusa Tenggara were taken as research samples. The overview of the results and discussion was further discussed.